Risk perception on the labour ward: A mixed methods study. Issue 2 (April 2021) - McCarthy, Claire; Meaney, Sarah; Rochford, Marie; O'Donoghue, Keelin
Healthcare providers commonly experience risky situations in the provision of maternity care, and there has been increased focus on the lived experience in recent years. We aimed to assess opinions on, understanding of and behaviours of risk on the LW by conducting a mixed methods study. Staff working in a LW setting completed a descriptive questionnaire-based study, followed by qualitative structured interviews. Statistical analysis was performed with SPSS on quantitative data and thematic analysis performed on qualitative data. Nearly two thirds of staff (64%; 73/114) completed the questionnaire, with 56.2% (n = 47) experiencing risk on a daily basis. Experiencing risk evoked feelings of apprehension (68.4%; n = 50) and worry (60.2%; n = 44) which was echoed in the qualitative work. Structured clinical assessment was utilised in risky situations, and staff described " going on autopilot " to manage these situations. A large number of respondents reflected on their provision of care following an adverse event (87.7%; n = 64). Debriefing was mentioned as an important practice following such events by all respondents. This study describes the negative terminology prevailing in emergency obstetric care. These experiences can have a profound impact on staff. Risk reduction strategies and the provision of increased staff support and training are crucial to improve staff wellbeing in stressful scenarios.